Paper from waste - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A method of making paper out of sugar-cane waste and banana stems has been developed by researchers at Japan's National Chemical Laboratory for Industries. The new process has environmental as well as economic advantages. Conventional paper-making...